2012
DOI: 10.1002/lapl.201110120
|View full text |Cite
|
Sign up to set email alerts
|

Experimental realization of counterfactual quantum cryptography

Abstract: In counterfactual quantum key distribution (CQKD) information is transferred, in a secure way, between Alice and Bob even when no particle carrying the information is in fact transmitted between them. In this letter we fully implement the scheme for CQKD proposed in [1], demonstrating for the first time that information can be transmitted between two parties without the transmission of a carrier

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 52 publications
0
47
0
Order By: Relevance
“…The schematic of the asymmetric QKD system shown in Fig. 1 is proposed by Brida [5] and looks different from the original schematic in Ref. [1].…”
Section: A Key-distributing Modementioning
confidence: 92%
See 2 more Smart Citations
“…The schematic of the asymmetric QKD system shown in Fig. 1 is proposed by Brida [5] and looks different from the original schematic in Ref. [1].…”
Section: A Key-distributing Modementioning
confidence: 92%
“…Then, a security proof against interceptresend attacks in a realistic situation was provided [3], and the experimental realizations of the N09 protocol have been proposed in succession [4][5][6]. A more recent research shows that the N09 protocol is vulnerable to a new Trojan horse attack owing to the unsatisfactory precision of the filters [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though counterfactual quantum cryptography may not be so useful for long-distance communication, it is interesting conceptually [104,105]. Schemes to improve the efficiency of counterfactual quantum key distribution protocols [106,107], security analysis of such schemes under various attacks such as intercept-resend and counterfactual attacks [108][109][110], experimental realisation using different set-ups [25,111,112], direct communication protocols [113] and counterfactual generation and distribution of entanglement [114] have contributed towards better understanding of applying counterfactuality. The basic idea of the direct communication protocol is to ensure counterfactual transfer of information using the chained beamsplitter approach mentioned earlier.…”
Section: Counterfactual Quantum Cryptographymentioning
confidence: 99%
“…Counterfactual quantum key distribution (CQKD) has also been investigated extensively since the first CQKD scheme was presented by Noh in 2009 [4]. Experimentally, CQKD with no particle transmitted has been realized by different research groups [5,6], and its unconditional security was proved in an ideal situation [7,8]. Recently, Salih et al [9] demonstrated that classical information can be transferred from the sender to the receiver without any particles traveling between them, which challenged the long-standing assumption that information transfer requires physical particles to travel between sender and receiver, and attracted much subsequent attention [10][11][12].…”
Section: Introductionmentioning
confidence: 99%